ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN METODE AKUNTANSI KONSERVATIF - Hasnawati Hasnawati; Christina Dwi Astuti (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2007)
This study analyzed about factors (ownership structure, debt covenant hypothesis, political cost hypothesis, growth and earnings management) that effect in choosing the conservatism of accounting method. In this study, conservatism is proxies by using minimum has two categories: 1)using average method in valuation of inventories, 2)using double declining balance method in depreciation of fixed assets, 3) using double declining balance method in amortization of intangible assets, and 4) research and development recognized as cost in current period. The object of this study is manufacturing and service companies (except banking, securities, insurance, properties and non banking Credit Agencies) listed at Jakarta Stock Exchange for 2002 - 2005 using purposive judgment sampling. Hypothesis test of this study using logistic regression method witha= 5% revealed that none of those factors effect in choosing conservatism of accounting method